Report on the current status of blue economy business sectors and development trends of key sectors - Tuomas Pohjola; Olena de Andres Gonzalez (Finnish Environment Institut, SYKE, 2022)
The aims of blue economy and the Blue Growth Agenda, in line with the Baltic Sea Region (EUBSR)
strategy, are major driving forces in the future Maritime Spatial Planning (MSP) processes. This
report outlines the current status of the selected blue economic businesses in the Plan4Blue (P4B)
project area in Finland and Estonia and depicts some possible development trends, based on their
ten-year past development. This analysis of the blue industry development is primarily based on
Orbis Europe database and national statistics databases. The sectoral development is illustrated with
graphs presenting turnover and employment figures development and some future trends in the P4B
project area in Finland and Estonia separately. All key sectors show positive long-term development,
tourism industry showing the strongest future growth potential in terms of expected number of
employees. In terms of productivity, the energy sector and marine construction sector are the highest
performers out of the selected blue industry sectors in the P4B project area. To better understand the
future development and sustainable growth potential of the selected blue industry sectors and coastal
regions, more research is suggested to be carried out.